Distribucion del biotipo B de Bemisia tabaci en la zona central de Panama - Alvarado G, L.=700 1 Sanchez S, J.; Zachriáon S, B.; Fernandez G, O.
(Es, En)
Ilus., 16 ref.
Keywords: BEMISIA TABACI; PLAGAS DE PLANTAS; RAPD; PCR; DISTRIBUCION GEOGRAFICA; PANAMA; MOSCA BLANCA